Letter to the Editor: A strange cloud in the Arctic summer stratosphere 1998 above Esrange (68°N), Sweden - Siebert, J.; Timmis, C.; Vaughan, G.; Fricke, K. H. (CCSD, 2000)
International audience When the University of Bonn lidar on the Esrange (68°N, 21°E), Sweden, was switched on in the evening of July 18, 1998, a geometrically and optically thin cloud layer was present near 14 km altitude or 400 K potential temperature, where it persisted for two hours. The tropopause altitude was 4 km below the cloud altitude. The cloud particles depolarized the lidar returns, thus must they have been aspherical and hence solid. Atmospheric temperatures near 230 K were approximately 40 K too high to support ice particles at stratospheric water vapour pressures of a few ppmv. The isentropic back trajectory on 400 K showed the air parcels to have stayed clear of active major rocket launch sites. The air parcels at 400 K had traveled from the Aleutians across Canada and the Atlantic Ocean arriving above central Europe and then turned northward to pass over above the lidar station. Parcels at levels at ±25 K from 400 K had come from the pole and joined the 400 K trajectory path above eastern Canada. Apparently the cloud existed in a filament of air with an origin different from those filaments both above and below. Possibly the 400 K level air parcels had carried soot particles from forest wild fires in northern Canada or volcanic ash from the eruption of the Korovin Volcano in the Aleutian Islands.